Enhancing Reading Motivation Through an Integrated Reading Approach: A Quasi-Experimental Study in Ethiopian Secondary Schools - Jarssa, Ammanuel Berhanu; Bushisso, Elias Woemego; Olamo, Taye Gebremariam (VELES Voices of English Language Education Society, 2025)
Low reading motivation remains as a challenge that still obstructs the way that students develop academically with texts. This study examines secondary school students' reading motivation, with a particular focus on the impact of an integrated reading approach that combines wide-ranging reading with intensive reading. The study had involved around 106 Grade 11 students within Bariso Dukale Secondary School located in Bule Hora. It was conducted throughout a 16-week semester for addressing limitations of customary rote-based instruction. Participants were in a convenient manner assigned into an experimental group (n = 54) and into a comparison group (n = 52). A certain quasi-experimental design was used throughout. On a weekly basis, the experimental group was given 40 minutes of integrated reading instruction that was supported through supplementary materials planned for the purpose of increasing engagement. The comparison group gave adherence to the conventional reading practices. With a validated questionnaire, researchers measured reading motivation, and the questionnaire included intrinsic interest, reading habits, and perceived competence. For the collection of qualitative understandings, eleven students were interviewed from the experimental group. When the data was being analyzed, independent-samples t-tests and paired-samples t-tests revealed the experimental group did improve greatly in reading motivation (p = 0.000). Interview responses further supported these particular findings, as well as highlighted additional enthusiasm, autonomy, plus engagement. These results show that integrating both intensive and wide-ranging reading improves student reading motivation.